Niger : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the IMF's projections and estimates on Niger's gross domestic product by sector at current market prices; gross domestic product of the modern and traditional sector at current market prices; gross domestic product at constant 1987 prices; government revenue and grants; monetary survey; summary accounts of the central and commercial banks; interest rates on money markets, during 1994-99; rediscount rates applied by the central bank, 1989-99; lending applied by commercial banks, 1988-99; deposit rates applied by the commercial banks, 1989-99; summary of the tax system, as of September 30, 2000, and so on.